login
E.g.f. satisfies A(x) = 2 - exp(-x*A(x)^2).
3

%I #11 Nov 07 2023 08:27:27

%S 1,1,3,13,55,-59,-8869,-230019,-4735569,-81845819,-925266221,

%T 11304277117,1342388191079,64570153427781,2378028350945547,

%U 68237841920780221,1044508709568828511,-45901762542718407035,-5887687395597254917885,-396339747040666473203907

%N E.g.f. satisfies A(x) = 2 - exp(-x*A(x)^2).

%F a(n) = (2*n)! * Sum_{k=0..n} (-1)^(n-k) * Stirling2(n,k)/(2*n-k+1)!.

%o (PARI) a(n) = (2*n)!*sum(k=0, n, (-1)^(n-k)*stirling(n, k, 2)/(2*n-k+1)!);

%Y Cf. A097718, A367154.

%Y Cf. A367078, A367080.

%K sign

%O 0,3

%A _Seiichi Manyama_, Nov 07 2023